L’ouverture contrastée d’un front écologique dans la Russie post-soviétique : la ceinture verte de Fennoscandie - Ian Florin (EchoGéo)
This article shows how actors united under the banner of the Fennoscandian Green Belt (GBF) combined environmental discourse and international relations to influence nature conservation policy in post-Soviet Russia. Based on documentary research and nearly seventy interviews, it traces how the GBF concept motivated and justified the opening of an ecofrontier along the borders between Russia, Finland and Norway in the name of protecting a supposedly pristine nature preserved by Cold War access restrictions. Adopting a critical geopolitics perspective, the article examines how environmental conservation is used to further the European Neighborhood Policy, which aims to position Russia as a key diplomatic partner by supporting its transition towards a liberal democratic model.